IMPLEMENTASI NILAI-NILAI KEARIFAN LOKAL PADA KESENIAN GENDANG BELEQ DALAM PEMBELAJARAN IPAS KELAS IV SDN 4 RUMBUK - Eka Julianti; Arif Rahman Hakimi,M.Pd; Andi Sulastri,M.Pd (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the implementation of local wisdom values in theGendang Beleq art form in fourth-grade science lessons at SDN 4 Rumbuk, identifyobstacles faced by teachers, and formulate solutions to overcome these obstacles.Using a qualitative case study approach, data were collected through observation,semi-structured interviews with teachers and students, and documentation. Datawere then analyzed using the Miles and Huberman model. The results of the studyindicate that teachers have implemented the values of Gendang Beleq, such asperseverance, discipline, cooperation, enthusiasm, cultural pride, and economicvalues, into the “Indonesiaku Kaya Budaya” (My Indonesia is Rich in Culture)science and studies material through a contextual approach, group discussions,experience sharing, and video screenings. However, this implementation facedseveral obstacles, including students’ lack of direct experience with Gendang Beleqart, limited learning media in the form of concrete demonstrations, a lack of localwisdom material in textbooks, and limited learning time. To overcome theseobstacles, teachers implemented various creative solutions, such as encouraginggroup discussions through “window information” activities, utilizing digital media(videos and images from the internet), focusing learning on relevant core values,independently developing additional teaching materials, and assigning individualand group assignments that connect learning to students' real lives. This studyconcludes that teachers' efforts to integrate Gendang Beleq local wisdomcontextually and adaptively successfully improved students' understanding andcharacter development, despite limited resources and time.